Крайові задачі для гіперболічних рівнянь зі сталими коефіцієнтами - Бобик, І.О.; Пташник, Б.Й. (Український математичний журнал, 1994)
By using a metric approach, the problem of correctness of a boundary-value problem is studied for a hyperbolic equation of order n (n ≥ 2) with constant coefficients defined in a tube domain. Existence and uniqueness conditions arc formulated in terms of number theory. We prove a metric theorem on lower estimates for small denominators that appear in solutions of the problem.